A review of the nematode genus Labiobulura (Ascaridida: Subuluridae) parasitic in bandicoots (Peramelidae) and bilbies (Thylocomyidae) from Australia and rodents (Murinae: Hydromyini) from Papua New Guinea with the description of two new species - Smales, Lesley R. (Zootaxa, 2009)
The nematode genus Labiobulura Skrjabin & Schikhobalova, presently known from bandicoots (Isoodon Desmarest and Perameles Geoffroy), and bilbies (Macrotis Reid) from Australia and rodents (Leptomys Thomas) from Papua New Guinea is revised. Diagnoses of Labiobulura, Labiobulura (Archeobulura) Quentin and Labiobulura (Labiobulura) Quentin and a key to all species of the genus are given. Five species are redescribed: L. (A.) leptomyidis Smales from L. paulus Musser, Helgen & Lunde, L. (A.) peragale Johnston & Mawson from M. leucura (Thomas), L. (L.) baylisi Mawson from I. macrourus (Gould) and P. nasuta Geoffroy, L. (L.) inglisi Mawson from I. obesulus (Shaw), P. bougainville Quoy & Gaimard and P. gunnii Gray, L. (L.) peramelis Baylis from I. macrourus and two are described as new: L. (A.) perditus from P. bougainville, L. (L.) quentini from I. obesulus and the identification of the hosts determined. The significance of the relationship between the placement of the amphids and cephalic papillae and the labial lobes is discussed and the denticles surrounding the mouth opening in the sub genus Labiobulura are described, both for the first time. There is evidence for host specificity in the Archeobulura with each parasite species limited to a single host species but less so for the Labiobulura with three of five species found in more than one host species.